UJI ORGANOLEPTIS DAN ANTIJAMUR OBAT KUMUR HYDROGEL KARAGENAN EUCHEMA SPINOSUM TERHADAP CANDIDA ALBICANS - Adipramana, Ibnu; Bakar, Abu; Afriza, Dhona (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Candida albicans is a normal fungal in the oral cavity that is commensal and is found in 40-80% of healthy humans, but can chance nto opportunistic pathogenic microorganisms under certain circumstances. The inhibition of Candida albicans can be treated by chemical drugs and it challenge to use herbal medicinal plants. Carrageenan (Eucheuma spinosum) is a natural ingredient that can be used as a medicinal and antifungal plant because it contains several secondary metabolite compounds such as flavonoids, tannins, saponins and alkaloids. However, carrageenan as an antifungal for the fungus Candida albicans is not known for certain. Therefore, the aim of this research was to determine the organoleptic and antifungal properties of carrageenan hydrogel mouthwash against the fungus Candida albicans. Then organoleptic, pH, viscosity and antifungal tests were carried out for carrageenan hydrogel mouthwash against Candida albicans fungi with concentrations of 0.5%, 1%, 2% and 4% as well as a positive control using 200mg ketoconazole and a negative control using distilled water. This study was carried out using a questionnaire, pH meter, Brookfield viscometer and paper discs. The results showed that the carrageenan hydrogel mouthwash with all formulations was acceptable to all respondences had a stable pH and viscosity, and there was no antifungal effect in the carrageenan hydrogel mouthwash against the inhibition zone of the Candidaalbicans. The carrageenan hydrogel mouthwash could be used as oral mouthwash by adding the other active component which possesses anticandidal activity.